Numerical Representations of Marine Ice‐Nucleating Particles in Remote Marine Environments Evaluated Against Observations. Issue 13 (12th July 2019) - McCluskey, C. S.; DeMott, P. J.; Ma, P.‐L.; Burrows, S. M.
Abstract: The abundance and sources of ice‐nucleating particles, particles required for heterogeneous ice nucleation, are long‐standing sources of uncertainty in quantifying aerosol‐cloud interactions. In this study, we demonstrate near closure between immersion freezing ice‐nucleating particle number concentration ( n INPs ) observations and n INPs calculated from simulated sea spray aerosol and dust. The Community Atmospheric Model with constrained meteorology was used to simulate aerosol concentrations at the Mace Head Research Station (North Atlantic) and over the Southern Ocean to the south of Tasmania (Clouds, Aerosols, Precipitation, Radiation, and atmospherIc Composition Over the southeRN ocean campaign). Model‐predicted n INPs were within a factor of 10 of n INPs observed with an off‐line ice spectrometer at Mace Head Research Station and Clouds, Aerosols, Precipitation, Radiation, and atmospherIc Composition Over the southeRN ocean campaign, for 93% and 69% of observations, respectively. Simulated vertical profiles of n INPs reveal that transported dust may be critical to n INPs in remote regions and that sea spray aerosol may be the dominate contributor to primary ice nucleation in Southern Ocean low‐level mixed‐phase clouds. Plain Language Summary: The clouds over remote oceans are often comprised of supercooled liquid droplets, but global models struggle to represent the complex processes that control ice formation in these clouds. One poorly understood, but critical, aspect controlling the liquid‐ice partitioning in these clouds is the abundance of particles that catalyze ice crystal formation, or ice‐nucleating particles (INPs). Observations show that INPs are extremely rare in remote marine environments and are dominated by an oceanic source. However, current global models do not account for these uniquely low INP concentrations and their marine source. We used observations of INPs from two previous field campaigns to evaluate INP concentrations estimated from a global climate model that incorporates particles from sea salt, marine organic matter, and mineral dust. Our results constitute an early evaluation of the potential of present‐day global atmospheric models to successfully predict INP concentrations in the lowest atmospheric level that feeds clouds over the ocean. Extrapolating our approach to higher altitudes, the model suggests mineral/soil dust particles from long‐range transport may also be a critical INP source for marine clouds. Key Points: Observed marine boundary layer ice‐nucleating particle concentrations were successfully predicted using marine and dust parameterizations Sea spray aerosol was the dominant source of simulated ice‐nucleating particle populations up to 3–5 km over the Southern Ocean Mineral dust aerosol was a critical component of model‐predicted ice‐nucleating particle populations present above 5 km